The effects of sensory stimulation therapy in patients with sleep disorders: a scoping review - Qu, Zihan; Sun, Xuefeng; Zhang, Xiaotu; Yin, Jiawei; Zhang, Xinye; Zhao, Haifeng; Zhang, Hongshi (Frontiers in Neuroscience, 2025)
BackgroundSleep disorders are prevalent, affecting 27% of the population and linked to health issues like cognitive impairments and cardiovascular diseases. Current treatments have limitations, prompting interest in sensory stimulation therapy as an alternative approach.ObjectiveThis scoping review aims to explore the effectiveness of sensory stimulation therapy as an intervention for improving sleep disorders, as well as its range of applicability, by synthesizing existing research.MethodsUsing the methodological framework of Arksey and O’Malley and following the PRISMA guidelines, both keywords and free-text searches were conducted. Articles meeting the inclusion criteria were then selected from the China National Knowledge Infrastructure Database, Wanfang Knowledge Service Platform Database, PubMed, Embase, Web of Science and Cochrane Library databases. Each article was screened and analyzed according to specific research elements.ResultsA total of 20 randomized controlled trials, involving 1489 participants across 2 types of sensory stimulation therapy, namely multi-sensory and single-sensory stimulations, were included in the study. The main sensory stimuli applied were auditory, visual, olfactory and tactile, while the intervention methods included music therapy, light therapy, aromatherapy and massage therapy. The intervention duration, frequency and cycles varied considerably, but most studies implementing individual sessions lasting 20–60 min, at least three sessions per week. Fourteen methods were used to assess sleep quality, and the majority of studies applied two or more assessment methods. Completion rates were also high, with 85%–100% of patients completing over 80% of the intervention protocol. Interestingly, 19 studies reported no adverse events. Overall, sensory stimulation therapy had a positive impact on sleep quality, particularly in aspects such as sleep latency, total sleep time, and subjective sleep experience.ConclusionThe results indicated that sensory stimulation therapy is a safe, feasible and beneficial intervention for improving sleep quality in patients with sleep disorders. However, several limitations were identified in the included studies. Future large-sample, multi-center, high-quality RCTs are needed to further verify the efficacy of this therapy, and provide stronger evidence for their clinical application.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/KQ2XT